Silent violence in the just transition: structural barriers, governance design, and the hidden costs of climate policy - Chigbu, Bianca Ifeoma; Makapela, Sicelo Leonard; Umejesi, Ikechukwu (Frontiers in Environmental Science, 2025)
The concept of silent violence refers to the hidden harm embedded in policy and economic systems, manifesting as the repression of activists, displacement of communities, and exploitation of labour across transitions to low-carbon economies. This article examines how structural barriers embedded in global just transition policies and energy governance frameworks produce forms of silent violence (SV) that disproportionately harm marginalized communities. Drawing on a comparative, multi-case analysis from Bolivia, Canada, South Africa, and Brazil, the study argues that SV is not accidental but a governance-enabled outcome, manifested through policy loopholes, non-consultative permitting, regulatory capture, and enforcement failures. Conceptually, SV is framed as a subset of structural violence that remains legally unframed, institutionally normalized, and largely invisible in climate policy discourse. The article advances a typology of silent violence, ranging from soft forms (epistemic exclusion, procedural marginalization) to hard forms (criminalization, state repression, and lethal harm). We introduce the Silent Violence Continuum as an analytical tool to map how different governance instruments condition escalating harms under the guise of sustainable development. The study contributes to critical climate justice scholarship by showing how SV operates as a design feature of transition governance rather than a failure. The article calls for the integration of silent violence metrics into climate policy evaluation to support more equitable, transparent, and non-violent transitions.